Decisive factors for indie publishers to win authors' hearts to publish their books - Anjaningrum, Widiya Dewi; Rahayu, Elisa Dwi; Viloria, Vivien Amor (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
Purpose – This study aimed to determine the significant impact of marketing stimuli on perceived usefulness, the appreciably effect of social media interaction on content quality, and the remarkably influence of perceived usefulness and content quality on purchase intentions.Design/methodology/approach – This is quantitative research, where quantitative data were obtained from the distribution of online questionnaires. The research sample was all participants of the